Investigation of Caffeine Degradation by Anodic Oxidation Using Boron-Doped Diamond Electrode - Değermenci, Gökçe Didar (Sakarya University Journal of Science, 2024)
In this study, the purification of caffeine by electrochemical oxidation, one of the advanced oxidation processes, was systematically investigated. A boron-doped diamond electrode was used as the anode, which has a high potential for the production of large amounts of hydroxyl radicals. The effects of applied current density, initial pH, supporting electrolyte concentration, cathode type, anode-cathode distance, and initial caffeine concentration were evaluated. The results showed that the electrochemical degradation rates of caffeine follow pseudo-first-order kinetics, with rate constants ranging from 0.0154 to 0.0496 min-1 depending on the operating parameters. The applied current density and the electrolysis time proved to be the most important parameters influencing both caffeine degradation and energy consumption. However, varying the initial caffeine concentration and the concentration of the supporting electrolyte also influenced the caffeine degradation rates. Changing the anode-cathode distance and the type of cathode has no effect on the rate of caffeine degradation, but it does have an effect on energy consumption. A current density of 20 mA cm-2, a supporting electrolyte concentration of 50 mM K2SO4, an anode-cathode distance of 2 mm, a cathode type of stainless steel, and an initial solution pH of 3 were found to be optimal values for the degradation of a solution containing 25 mg L-1 caffeine in 45 minutes using a boron-doped diamond anode. Finally, it was found that the pH value of the solution tended to increase during electrolysis.
Keywords: boron-doped diamond; Anodic oxidation; Caffeine removal; Boron-Doped diamond; anodic oxidation; Environmental Engineering (Other); Engineering (General). Civil engineering (General); caffeine removal; Chemistry; Çevre Mühendisliği (Diğer); TA1-2040; QD1-999; 7. Clean energy; 3. Good health